A Classificacao Internacional de Doencas, a Familia de Classificacoes Internacionais, a CID-11 e a Sindrome Pos-Poliomielite - Ruy Laurenti; Heloisa Brunow Ventura Di Nubila; Abrahao Augusto Joviniano Quadros; Monica Tilli Reis Pessoa Conde; Acary Souza Bulle Oliveira (Arquivos de Neuro-Psiquiatria)
The first International Classification of Diseases (ICD) was approved in 1893 and since then it has been periodically reviewed. The last, 10th revision (ICD-10), was approved in 1989. Since 1989, it was possible to update from ICD revisions, which did not happen before. The next revision (ICD-11) would probably be published in 2015. In 1989, mechanisms were established to update ICD-10, through the creation of the Morbidity Reference Group (MbRG) in 1997 and the Update and Revision Committee (URC) in 2000. The Morbidity Reference Group (MbRG) was created in 2007 to discuss in more detail the issues to update morbidity. A specific code in ICD was not included in the revision of ICD-10 in 1989 for the post-polio syndrome (PPS). However, the ICD new code G14 for PPS was included in ICD-10 since 2010.